The Influence of Kind of Hormone to Level of Sheep Oocytes Matured in Vitro - Wattimena, J; Saija, ME (ANIMAL PRODUCTION, 2005)
The objectives of the research were to know the effect of various hormone on in vitro maturation ovine oocyte. The result was expected to give information about the effect of various hormone on in vitro maturation ovine oocyte. The result of research show that treatment no significant (P>0.05) influenced on germinal vesicle (GV), germinal vesicle breakdown (GVBD) and metaphase-I (M-I) phase. The treatment P3 (CR1aa+FSH+ Estradiol+hCG) significant (P<0.05) increased maturation rate then P1 (CR1aa+FSH) dan P2 (CR1aa+FSH+ Estradiol). (Animal Production 7(3): 194-197 (2005)Â Key words : Hormone, Oocyte Maturation, Sheep, In Vitro